Augmented reality in vocational mechanical engineering education: a systematic literature review - Ahda Sabila; refdinal refdinal; Waskito Waskito; Hansi Effendi; Khofifah Alawyah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The integration of Augmented Reality (AR) in vocational and mechanical engineering education has become increasingly important in the era of Industry 4.0, where digital competence and practical skills are essential. This systematic literature review aims to identify research trends, methodologies, learning contexts, and challenges related to the use of AR in vocational mechanical engineering education. Guided by the PRISMA framework, a total of 13 empirical studies published between 2020 and 2025 were collected from Scopus and ScienceDirect databases and analysed based on research design, learning topics, and educational outcomes. The findings reveal that most studies employed quasi-experimental and R&D approaches, integrating AR into subjects such as mechanical systems, thermodynamics, structural analysis, CNC machining, and engineering drawing. Across these studies, AR consistently improved learning achievement, spatial reasoning, motivation, and engagement. However, common challenges included hardware limitations, model precision issues, usability constraints, and a lack of teacher readiness. These results highlight AR’s strong potential to enhance technical learning experiences and bridge the gap between theoretical and practical understanding in vocational engineering education.